2023
DOI: 10.1007/s00264-022-05663-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of extended reality on surgery: a scoping review

Abstract: Purpose Extended reality (XR) is defined as a spectrum of technologies that range from purely virtual environments to enhanced real-world environments. In the past two decades, XR-assisted surgery has seen an increase in its use and also in research and development. This scoping review aims to map out the historical trends in these technologies and their future prospects, with an emphasis on the reported outcomes and ethical considerations on the use of these technologies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 87 publications
2
26
0
1
Order By: Relevance
“…One recent scoping review examined the role of VR and AR in a clinician-as-user, patient-specific manner, albeit with broader criteria than in this review: It included studies that examined any surgical application of any specialty, including those examining applications in medical education as well as experiments conducted with cadavers. Consistent with the findings of this review, the implementation of extended reality was reported to contribute to the surgical field by enhancing intraoperative spatial awareness and reducing the risk of iatrogenic injury [ 55 ]. In further alignment with this review’s findings, the authors concluded that there is a significant need for further studies—particularly requiring more data reported with respect to the quantification of the accuracy of operative plans and outcomes using these extended reality applications [ 55 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…One recent scoping review examined the role of VR and AR in a clinician-as-user, patient-specific manner, albeit with broader criteria than in this review: It included studies that examined any surgical application of any specialty, including those examining applications in medical education as well as experiments conducted with cadavers. Consistent with the findings of this review, the implementation of extended reality was reported to contribute to the surgical field by enhancing intraoperative spatial awareness and reducing the risk of iatrogenic injury [ 55 ]. In further alignment with this review’s findings, the authors concluded that there is a significant need for further studies—particularly requiring more data reported with respect to the quantification of the accuracy of operative plans and outcomes using these extended reality applications [ 55 ].…”
Section: Discussionsupporting
confidence: 69%
“…Consistent with the findings of this review, the implementation of extended reality was reported to contribute to the surgical field by enhancing intraoperative spatial awareness and reducing the risk of iatrogenic injury [ 55 ]. In further alignment with this review’s findings, the authors concluded that there is a significant need for further studies—particularly requiring more data reported with respect to the quantification of the accuracy of operative plans and outcomes using these extended reality applications [ 55 ].…”
Section: Discussionsupporting
confidence: 69%
“…For time to task completion and technical scores, XR enhances procedural accuracy and surgical confidence by facilitating a deeper understanding of the patient's anatomy. 21 The integration of XR in surgical procedures holds potential therapeutic benefits, particularly for complex cases [18][19][20]54,55 because the learning curve is high. There is evidence that learning curves for complex procedures can be mitigated with repetition and motivation 56 and intelligent tutoring systems.…”
Section: Discussionmentioning
confidence: 99%
“…In orthopaedic trauma surgery, different modalities of reality technologies are currently available to support procedural teaching, practice, and patient-specific simulations, namely, virtual reality (VR), augmented reality, and mixed reality. These three reality modalities may sometimes be collectively described with the umbrella term extended reality [ 28 ] ( Figure 1 ). VR systems provide total visual immersion, movements, and interactions in an artificial, computer-generated environment that may incorporate artificial stimuli such as sounds or hand-operated controllers to improve the interactive experience [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…While VR employs an entirely artificial computer-generated environment, augmented reality superimposes digital images onto physical environments in real-time. The term augmented virtual reality is also used distinctively in some literature to describe the real-time representation of physical world events in a virtual environment [ 28 ]. On the other hand, mixed reality utilises a digital display overlay in conjunction with interactive projected holograms, allowing the operator to explore the physical environment while simultaneously interacting with and controlling the digital material provided by the device.…”
Section: Introductionmentioning
confidence: 99%